2016
DOI: 10.2147/jbm.s80646
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of romiplostim for treatment of immune thrombocytopenia

Abstract: Inhibition of platelet production and mediated by antiplatelet antibodies is a well-known mechanism causing low platelet counts in immune thrombocytopenia (ITP). Use of thrombopoietin receptor agonists increases platelet counts and decreases the risk of bleeding in patients with ITP. Two such thrombopoietin receptor agonists, romiplostim and eltrombopag, are approved by the US Food and Drug Administration to treat thrombocytopenia in adults, and most recently, children with persistent or chronic ITP. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In the present study, it was shown that the optimum dose of RP was 50 μg/kg of body weight/day (Fig. 1A ), which is 50-fold higher than the clinically used dose (1 μg/kg of body weight/day) but within the range showing no toxicity 26 . Moreover, in our preliminary trials using X-rays to overcome mortality due to 8 Gy of irradiation, mice that received 50 µg/kg of RP twice per day (12-hour intervals) for 3 consecutive days achieved a 100% 30-day survival rate (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…In the present study, it was shown that the optimum dose of RP was 50 μg/kg of body weight/day (Fig. 1A ), which is 50-fold higher than the clinically used dose (1 μg/kg of body weight/day) but within the range showing no toxicity 26 . Moreover, in our preliminary trials using X-rays to overcome mortality due to 8 Gy of irradiation, mice that received 50 µg/kg of RP twice per day (12-hour intervals) for 3 consecutive days achieved a 100% 30-day survival rate (data not shown).…”
Section: Discussionmentioning
confidence: 47%
“…Longer-term nonrandomized observational studies have suggested a modestly higher rate of thrombosis in patients with ITP treated with TPO-RAs as compared with similar observational studies of patients with ITP treated with immunosuppressive agents. 57,58 Therefore, the thrombotic potential of TPO-RAs should be a consideration in patients with ITP with significant risk factors for venous or arterial thrombosis.…”
Section: What Adverse Events Occur and How To Monitor For Themmentioning
confidence: 99%
“…The endothelial recirculation of the crystallized domain elongates the half-life of the polypeptide [34]. Subcutaneous administration of romiplostim increases platelet count and reduces bleeding episodes in ITP patients [35]. With an aim to evaluate the efficacy of romiplostim by measuring the stable platelet response and safety of treatment, two parallel placebo-controlled Phase III trials, involving splenectomized and non-splenectomized ITP patients, with mean three platelet count ≤30 X 109/L were conducted.…”
Section: Reviewmentioning
confidence: 99%
“…No antibodies against romiplostim or thrombopoietin were produced. Side effects were alike in both the romiplostim and placebo-treated groups [35-36]. Only two romiplostim-treated patients reported adverse reactions involving increased bone marrow reticulin in one patient and peripheral disease and atrial fibrillation in another patient.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation